Insights Into the Effects of Mucosal Epithelial and Innate Immune Dysfunction in Older People on Host Interactions With Streptococcus pneumoniae - Weight, Caroline M.; Jochems, Simon P.; Adler, Hugh; Ferreira, Daniela M.; Brown, Jeremy S.; Heyderman, Robert S. (Frontiers in Cellular and Infection Microbiology, 2021)
In humans, nasopharyngeal carriage of Streptococcus pneumoniae is common and although primarily asymptomatic, is a pre-requisite for pneumonia and invasive pneumococcal disease (IPD). Together, these kill over 500,000 people over the age of 70 years worldwide every year. Pneumococcal conjugate vaccines have been largely successful in reducing IPD in young children and have had considerable indirect impact in protection of older people in industrialized country settings (herd immunity). However, serotype replacement continues to threaten vulnerable populations, particularly older people in whom direct vaccine efficacy is reduced. The early control of pneumococcal colonization at the mucosal surface is mediated through a complex array of epithelial and innate immune cell interactions. Older people often display a state of chronic inflammation, which is associated with an increased mortality risk and has been termed ‘Inflammageing’. In this review, we discuss the contribution of an altered microbiome, the impact of inflammageing on human epithelial and innate immunity to S. pneumoniae, and how the resulting dysregulation may affect the outcome of pneumococcal infection in older individuals. We describe the impact of the pneumococcal vaccine and highlight potential research approaches which may improve our understanding of respiratory mucosal immunity during pneumococcal colonization in older individuals.